2007
DOI: 10.1121/1.2767000
|View full text |Cite
|
Sign up to set email alerts
|

Spectral and temporal cues for phoneme recognition in noise

Abstract: Cochlear implant users receive limited spectral and temporal information. Their speech recognition deteriorates dramatically in noise. The aim of the present study was to determine the relative contributions of spectral and temporal cues to speech recognition in noise. Spectral information was manipulated by varying the number of channels from 2 to 32 in a noise-excited vocoder. Temporal information was manipulated by varying the low-pass cutoff frequency of the envelope extractor from 1 to 512 Hz. Ten normal-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 30 publications
3
56
2
Order By: Relevance
“…This effect could have caused consonant and sentence intelligibility in the present study to drop substantially at þ5 dB SNR. The same effect was not observed for vowel intelligibility in the present study, presumably since vowel intelligibility relies strongly on spectral cues at all noise levels (Xu and Zheng, 2007) and was already affected even at þ15 dB SNR.…”
Section: Consonant Intelligibilitysupporting
confidence: 47%
“…This effect could have caused consonant and sentence intelligibility in the present study to drop substantially at þ5 dB SNR. The same effect was not observed for vowel intelligibility in the present study, presumably since vowel intelligibility relies strongly on spectral cues at all noise levels (Xu and Zheng, 2007) and was already affected even at þ15 dB SNR.…”
Section: Consonant Intelligibilitysupporting
confidence: 47%
“…Many studies in the literature have suggested that speech recognition in noise is dependent on spectral resolution to a greater degree than speech recognition in quiet. Vocoder studies have suggested that a substantially increased number of channels is needed for listening in noise backgrounds (Dorman et al, 1998;Xu and Zheng, 2007), particularly for vowel and voice pitch perception (approximately > 20 channels) (Kong and Zeng, 2006). The effective number of channels in a cochlear implant has found to be much lower (i.e., $8) than the number of implanted electrodes (Friesen et al, 2001).…”
Section: B Effects Of Neural Survival On Speech Recognition In Noisementioning
confidence: 99%
“…Temporal envelope modulations suffice to provide intelligible speech for as few as four spectral channels under ideal conditions ͑Shannon et al., 1995;Dorman et al, 1997͒. However, when the channels' envelope modulations are low-pass filtered with cutoff frequencies in the 8-16 Hz range, intelligibility decreases ͑Fu and Shannon, 2000;Xu and Zheng, 2007͒. Reverberation, which can act as a low-pass filter for envelope modulations in this frequency range ͑Houtgast and Steeneken, 1985͒, has similarly been shown to degrade intelligibility for listening through actual or simulated implants in rooms that listeners with normal hearing would find acceptable ͑Iglehart, 2004; Poissant et al, 2006͒. Studies of intelligibility for implant users in reverberant spaces have typically focused on the use of frequency modulation ͑FM͒ or sound field devices to improve intelligibility ͑Crandell et Iglehart, 2004;Anderson et al, 2005͒, with mixed results.…”
Section: Introductionmentioning
confidence: 99%